2001
DOI: 10.1046/j.1461-9555.2001.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of the pine engraver, Ips pini (Say) (Coleoptera: Scolytidae), to conophthorin and other angiosperm bark volatiles in the avoidance of non‐hosts

Abstract: 1 Seventeen non-host angiosperm bark volatiles, seven of which are antennally active to Ips pini (Say), the pine engraver (PE), were tested for their ability to disrupt the response of the PE to pheromone-baited traps. 2 Four green leaf volatiles (GLVs) were tested [1-hexanol (Z)-3-hexen-1-ol, hexanal, and (E)-2-hexenal]. None had any disruptive effect singly, as a group or in all possible blends based on functional groups, despite the fact that the two aldehydes were antennally active. These compounds may hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
1
34
0
Order By: Relevance
“…This compound was behaviorally inactive Behavioral and electrophysiological responses of Hylastinus obscurus to volatiles released for males, but all of the tested doses repelled females as effectively as R-limonene and S-limonene. Shown to be a green-leaves volatile by Thiéry and MarionPoll (1998), the inclusion of hexanal did not significantly reduce the attractiveness of traps baited with pheromones from Conophthorus resinosae (de Groot and MacDonald, 1999) and Ips pini (Huber et al, 2001). In fact, Jaffé et al (1993) showed that hexanal synergized a mix of different pineapple and coconut volatiles, which attracted palm weevils, Rhynchophorus palmarum, in laboratory assays, but not in field tests.…”
Section: Discussionmentioning
confidence: 96%
“…This compound was behaviorally inactive Behavioral and electrophysiological responses of Hylastinus obscurus to volatiles released for males, but all of the tested doses repelled females as effectively as R-limonene and S-limonene. Shown to be a green-leaves volatile by Thiéry and MarionPoll (1998), the inclusion of hexanal did not significantly reduce the attractiveness of traps baited with pheromones from Conophthorus resinosae (de Groot and MacDonald, 1999) and Ips pini (Huber et al, 2001). In fact, Jaffé et al (1993) showed that hexanal synergized a mix of different pineapple and coconut volatiles, which attracted palm weevils, Rhynchophorus palmarum, in laboratory assays, but not in field tests.…”
Section: Discussionmentioning
confidence: 96%
“…For example, in GC-EAD analyses of Betula pendula Roth, B. pubescens Ehrh and Populus tremula L. leaf and bark volatiles, the antennae of I. typographus strongly responded to C 6 -alcohols (GLVs): 1-hexanol and (Z)-3-hexen-1-ol from both leaves and bark, and (E)-2-hexen-1-ol from the nonhost intact leaves (Zhang et al, 1999a and to trans-conophthorin (tC) and C 8 -alcohols: 3-octanol and 1-octen-3-ol from the nonhost bark . NHVs from natural materials (Schroeder, 1992;Byers et al, 1998Byers et al, , 2000 or from dispensers with individual or blends of synthetic chemicals disrupt the responses of over 20 species of conifer bark beetles to their aggregation pheromones or host kairomones (Dickens et al, 1991(Dickens et al, , 1992aWilson et al, 1996;Guerrero et al, 1997;Huber et al, 1999, Zhang et al, 1999bPoland & Haack, 2000;Schlyter et al, 2000;Huber et al, 2000bHuber et al, , 2001Huber & Borden, 2001a,b;.…”
Section: Introductionmentioning
confidence: 99%
“…There is some existing evidence that bark and ambrosia beetles display positive, or at least not negative chemotaxis, to mixtures of nonhost volatiles and pheromone components (Deglow & Borden 1998a,b;Huber et al 2001). Huber et al (2001) hypothesized that bark beetles foraging for host material that was shrouded in leafy plants may often encounter mixtures of green leaf volatiles (GLVs) and conspecific aggregation pheromone components.…”
Section: Discussionmentioning
confidence: 99%
“…Huber et al (2001) hypothesized that bark beetles foraging for host material that was shrouded in leafy plants may often encounter mixtures of green leaf volatiles (GLVs) and conspecific aggregation pheromone components. Since it would be beneficial for the foraging beetle to orient towards the shrouded host, it may display positive chemotaxis or may Vol.…”
Section: Discussionmentioning
confidence: 99%